FROM THE FORMULA “TO THE GLORY OF GOD THE FATHER” (PHIL 2:11) TO THE FORGOTTEN THEOLOGY OF PHIL 2:6-11 AS PAULINE FORMULA FOR MONOTHEISM - Ayeni, Ayodele (Science et Esprit, 2021)
The debates around the structure of Phil 2:5/6-11 led to the neglect of the theology of Phil 2:6-11, to a near exclusive Christological reading of it. Ralph P. Martin’s title for Phil 2:6-11, “Carmen Christi” (“Christ’s Hymn”) puts a final stamp on the works of structuralists’ reading of Phil 2:6-11. I contend that that title is misleading, when one considers that “God” is mentioned explicitly four times in Phil 2:6-11 and “Jesus” only twice. In part two of this article, I further demonstrate that Philippians is a theological letter, in the service of identity formation.